The managerial socio-emotional competencies and the organizational climate in educational institutions - Condori Gutiérrez, Juan Luis (2021)
The article aims to describe the socio-emotional competencies that are outlined in managers, framed from a positive leadership approach, which is a perspective oriented towards continuous learning and that directly influences the balance of relationships between members of the community educational. Managers who resolve situations in which the emotional states of both teachers, students and parents are involved, have a favorable impact, influencing the improvement of the organizational climate, increasing the quality of relationships between members of the educational institution. The thematic development of the article begins with the conceptual approaches on socio-emotional competencies and organizational climate. Then, two proposals for the organization of the manager's socio-emotional competencies are presented; the first takes as a starting point the Framework for Good Executive Performance, a document prepared by the Ministry of Education, which identifies competence and performance related to socio-emotional traits. The second proposal is of a synthetic nature and is oriented to the intrapersonal and interpersonal dimensions, with results for decision-making. Finally, the reflection of both proposals is carried out, guiding their progress in the reality of educational institutions, as well as their relevance in the development of the organizational climate and its relationship with educational leadership.